Golden Agri resources and sustainability - Richards, Kenneth, (SAGE Knowledge. Cases., 2017)
While the use of palm oil has been documented since ancient times, it is only in the past few decades that this tropical product has taken off in the international market. An invisible component of many products, palm oil can be found in cookies, in chocolates, in soaps, in shampoos, and even in biofuel. This wide range of uses has stimulated cultivation and oil extraction; annual global production has increased more than nine-fold since 1980. By the 2000s, palm oil had become the most heavily traded edible oil in the world.